Problems and traffic impacts from floating population in Pattaya - Chanasit, Jaraspol; Sookhom, Arpaporn; Sookhom, Araya; Boonsuaykhwan, Rong; Krivart, Kittachet (Journal for Developing the Social and Community, 2025)
Background and Objectives: Floating population is a major obstacle to the development of the quality of public services, especially in solving traffic congestion problems in big cities, including Pattaya, which is an important economic and tourism center of the country. As a result, many floating populations migrate to work in the area. This study, therefore, aims to study the number and distribution of floating populations and study travel patterns, problems, and traffic impacts from travel of floating populations. Research Methodology: This research used a quantitative research method by counting the number of vehicles traveling through 6 points into Pattaya City between 6:30 - 8:30 a.m. and between 4:30 - 6:30 p.m. and using a questionnaire to collect data from a sample of 900 establishments/agencies with a hidden population working there. Statistics, frequency distributions, percentages, and maps showing the number and distribution were used to analyze the data. Research results: The floating population in Pattaya City is 459,847 people, an increase of 68,308 people from the survey in 2023. Most of the floating population is daytime floating population, accounting for 59.14 percent, while the nighttime floating population is 40.86 percent. The distribution of the floating population is densest in Survey Area 3 and Survey Area 4, which are located in the south. The study results of the direction and routes with heavy traffic from the counting of vehicles traveling into Pattaya City, there are 6 points, consistent with the problems and impacts of traffic congestion both in the morning and evening on Sukhumvit Road and the route connecting the east and west sides of Pattaya City, especially in areas that are intersections. Conclusion: The floating population in Pattaya City is 459,847 people, an increase of 68,308 people from the survey in 2023. As a result of the large floating population in the area, traffic congestion occurs both in the morning and evening on Sukhumvit Road, the connecting route on the east and west sides of Pattaya City, and the area that is the intersection.